ANALISIS PENYELENGGARAAN MAKANAN DAN KONTRIBUSI MAKANAN TERHADAP PERSEN LEMAK TUBUH DI SKADRON PENDIDIKAN 504 - Asalwa, Nabila; Swamilaksita, Prita Dhyani; Ronitawati, Putri (Lembaga Penerbitan Unversitas Esa Unggul, 2019)
AbstractBackground: Percent of body fat students in the dormitory can be influenced by several factors, including the influence of organizing food and the contribution of food from outside. The aim of this study is to analyze the food management system and the contribution of food from outside the hostel on the body fat percent of students in the Education Squadron 504. Method: Quantitative research and the design of this study is cross sectional in the form of observational studies. The total sample of Educational Squadron students 504 was 35. Results: Food management system which includes input, process, output, feedback and control in the 504 Education Squadron does not meet the food management standards. There is a relationship between contributions of energy, fat, and carbohydrate intakeoutsidethe hostel with body fat percent and has a moderate negative correlation (p <0.05). However, there was no significant relationship between the contribution of protein intake from outside the hostel with percent body fat (p> 0.05). Conclusion: There is a relationship between the contribution of energy in take, fat,and carbohydrates from out side the hostel to the percent body fat.Â Keywords: Food delivery system, contribution food from outside dormitory, body fat percentÂ AbstrakPersen lemak tubuh siswa diasrama dapat dipengaruhi oleh beberapa faktor, diantaranya adalah pengaruh penyelenggaraan makanan dan kontribusi makanan dari luar. Tujuan penelitian ini adalah menganalisis sistem penyelenggaraan makanan dan kontribusi makanan dari luar asrama terhadap persen lemak tubuh siswa di Skadron Pendidikan 504. Metode : Penelitian kuantitatif dan desain penelitian ini adalah crosssectional dalam bentuk studi observasional. Jumlah sampel siswa Skadron Pendidikan 504 yaitu 35 orang. Uji analisis bivariat yang digunakan adalah uji korelasi Spearman. Hasil: Sistem penyelenggaraan makanan yang meliputi input, proses, output, feedback serta kontrol di Skadron Pendidikan 504 belum memenuhi standar manajemen penyelenggaraan makanan. Terdapat hubungan antara kontribusi asupan energi, lemak, dan karbohidratdari luar asrama dengan persen lemak tubuh dan mempunyai korelasi negative sedang (p<0.05). Namun, tidak terdapat hubungan yang signifikan antara kontribusi asupan protein dari luar asrama dengan persen lemak tubuh (p>0.05).Kesimpulan: Terdapat hubungan antara kontribusi asupan energi, lemak, dan karbohidrat dari luar asrama terhadap persen lemak tubuh.Â Kata kunci: Sistem penyelenggaraan makanan, kontribusi makanan dari luar asrama, persen lemak tubuh